New Trends on Vanadium Chemistry, Biochemistry, and Medicinal Chemistry - Gambino, Dinorah (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The recognition of the exceptional chemical and biological properties of vanadium compounds has led, in recent decades, to extensive research exploring their chemistry, biochemistry, and medicinal chemistry. Due to the prospective application of vanadium compounds as therapeutic agents against diseases such as diabetes, cancer and those provoked by parasites and bacteria, vanadium coordination chemistry and biochemistry has been an area of extensive research. Currently, the most promising potential uses of vanadium compounds are as nutritional supplements and as anticancer agents potentiated by immunotherapy. Nevertheless, researchers from all over the world are dedicating their efforts to vanadium research related to other potential therapeutic applications of vanadium compounds and to obtain insights into their beneficial effects on health and their modes of action. This Special Issue collected research contributions focused on recent advances in vanadium chemistry, biochemistry, and medicinal chemistry. I expect that this collection will have a great impact on the future direction of vanadium research.